Are weight loss and metabolic outcomes of bariatric surgery influenced by candidate glucocorticoid receptor gene polymorphisms? A prospective study - Zohaib Iqbal; Senthil Kandaswamy Vasan; Helene Fachim; John Warner-Levy; Rachelle P. Donn; Basil J. Ammori; Adrian H. Heald; Handrean Soran; Akheel A. Syed (Adipocyte)
Background Bariatric surgery is the most effective treatment for severe obesity. There can be variation in the degree of weight reduction following bariatric surgery. It is unknown whether single nucleotide polymorphisms (SNPs) in the glucocorticoid receptor locus (GRL) affect postoperative weight loss and metabolic outcomes.Materials/methods We studied the association between selected candidate SNPs and postoperative weight loss and metabolic outcomes in patients with severe obesity undergoing bariatric surgery. The polymorphisms rs41423247 (Bcl1), rs56149945 (N363S) and rs6189/rs6190 (ER22/23EK) were analysed.Results The 139 participants included 95 women (68.3%) and had a median (interquartile range) age of 53.0 (46.0–60.0) years and mean (SD) weight of 140.8 (28.8) kg and body mass index of 50.3 (8.6) kg/m2. At baseline, 59 patients had type 2 diabetes (T2D), 60 had hypertension and 35 had obstructive sleep apnoea syndrome treated with continuous positive airway pressure (CPAP). 84 patients (60.4%) underwent gastric bypass and 55 (39.6%) underwent sleeve gastrectomy. There were no significant differences in weight loss, glycated haemoglobin (HbA1c) or lipid profile categorized by genotype status, sex or median age. There was significant weight reduction after bariatric surgery with a postoperative BMI of 34.1 (6.8) kg/m2 at 24 months (p < 0.001).Conclusion While GRL polymorphisms with a known deleterious effect on adipose tissue mass and function may have a small, additive effect on the prevalence of obesity and related metabolic disorders in the population, we suggest that the relatively weak biological influence of these SNPs is readily overcome by bariatric surgery.